LEVELS OF STUDENTS’ MATHEMATICS ANXIETIES AND THE IMPACTS ON ONLINE MATHEMATICS LEARNING - Siti Lailiyah; Sihhatul Hayat; Siti Urifah; Maunah Setyawati (LPMPP Universitas Negeri Yogyakarta, 2021)
It is widely assumed that anxieties tend to lead to low mathematics performance. The purpose of this study was to describe the levels of students’ mathematics anxieties and the impacts on mathematics learning achievement in online mathematics learning. The study was a quantitative survey. The research instrument was questionnaire consisting of four elements of physiological, cognitive, affective, and behavioral aspects. The subjects were 109 mathematics education students who were willing to be the research participants. The data were collected using mathematics anxiety questionnaires and documentation of students’ mathematics learning achievement. The data analyses used descriptive statistics and confirmatory factor analysis with structural equation modeling of the Lisrel program. The findings show that the levels of all aspects of students’ mathematics anxieties in online mathematics learning were at the moderate level. The anxiety aspects that affect students’ mathematics learning achievement in online mathematics learning were of the affective and cognitive categories, while the physiological and behavioral aspects do not affect mathematics learning achievement. A research implication is for the teacher to pay attention to the cognitive and affective aspects of the students’ mathematics anxieties.